Adjuvant anti-angiogenic therapy enhances chemotherapeutic uptake in a murine model of head and neck cancer*. (7th February 2019) - Prince, Andrew C.; Patel, Neel G.; Moore, Lindsay S.; McGee, Andrew S.; Ahn, John C.; Willey, Christopher D.; Carroll, William R.; Rosenthal, Eben L.; Warram, Jason M.
Abstract: Intratumoural metabolic demands result in excessive angiogenic cytokine release leading to unorganised vasculature. Resultant fluid dynamics oppose blood flow and drug penetration due to a marked increase in interstitial fluid hydrostatic pressure. It is hypothesised that anti-angiogenic therapy may function to 'prune' vasculature and lead to improved chemotherapeutic penetration. Subcutaneous, OSC19 tumour bearing mice ( n = 5/dose/agent) were administered varying doses of an anti-mouse VEGFR2 (DC101) or an anti-mouse VEGFR3 (31C1) –3 d, –1 d, 0 d, +1 d and +3 d prior to 200 µg of cetuximab fluorescently labelled with IRDye800CW. Fluorescence imaging of tumours was performed 10 d post cetuximab-IRDye800CW dose to monitor therapeutic uptake. Co-administration of dual anti-angiogenic agents at 50–50%, 75–25% and 25–75% using optimal dose and time (–1 d 10 mg/kg anti-VEGFR2 and –1 d 40 mg/kg anti-VEGFR3) was also evaluated. In order to establish vessel normalisation, NG2 (pericyte marker) and CD31 (endothelial cells) ratios were assessed during immunohistochemical staining of tumour sections. Twenty-mg/kg anti-VEGFR3 + 5 mg/kg anti-VEGFR2 significantly ( p < .0005) reduced tumour size (–73%) compared to control (59%). The 20 mg/kg anti-VEGFR3 + 5 mg/kg anti-VEGFR2 and 30 mg/kg anti-VEGFR3 + 2.5 mg/kg anti-VEGFR2 significantly ( p < .0004) improved percent-injected cetuximab-IRDye800CW dose/gram tumour tissue compared to other groups. Adjuvant, dual anti-angiogenic therapy targeting VEGFR2 and VEGFR3 significantly enhances tumour chemotherapeutic uptake compared to control.